Temporal Changes in Serum S100B Levels From Prehospital to Early In-Hospital Sampling in Patients Suffering Traumatic Brain Injury - Seidenfaden, Sophie-Charlott; Kjerulff, Julie Linding; Juul, Niels; Kirkegaard, Hans; Fogh Møller, Mette; Bloch Münster, Anna-Marie; Thingemann Bøtker, Morten (Frontiers in Neurology, 2022)
Background The biomarker S100B is used for the rule-out of intracranial lesions in patients with mild traumatic brain injury (TBI) and is suggested for prehospital use in Europe. Early kinetics of S100B are not exhaustively investigated in human TBI. This post hoc descriptive study of the data from the PreTBI studies aimed to characterize the early temporal changes of S100B using two-sample timepoints. Materials and Methods Two consecutive blood samples were taken prehospital and in-hospital after injury and assayed for S100B. The endpoint adjudication of the outcome intracranial lesion was done by the evaluation of electronic medical patient journals. The data were analyzed using descriptive statistics, scatterplots, and temporal changes estimated by the locally weighted scatterplot smoothing (LOWESS) regression line. Results A total of 592 adult patients with TBI were included; 566 with Glasgow Coma Scale (GCS) 14-15, 20 with GCS 9-13, and 6 with GCS 3-8. Intracranial lesions were diagnosed in 44/566 (7.4%) of patients. In 90% of patients, S100B concentrations decreased from prehospital to in-hospital sampling. The mean decrease was−0.34 μg/L. S100B concentrations seem to decline already within 60 min. Patients sampled very close to trauma and patients suffering intracranial lesions may express a slight incline before this decline. Temporal changes of S100B did not differ in patients >65 years of age, in antiplatelet/-coagulant treatment, alcohol intoxicated, or suffering extra-cranial injuries. Conclusion S100B concentrations may peak earlier than expected from previous studies of temporal changes in human TBI. Patterns of S100B stand robust to parameters stated as limiting factors to the use for early rule-out of intracranial lesions in the current guidelines. Further studies are needed to investigate the ultra-early temporal profiles of other novel TBI biomarkers to assess prehospital applicability and optimal diagnostic performance in TBI.